Вплив електромагнітного поля Wi-Fi систем та експериментального приладу M4 на процеси росту, розвитку та фотосинтез пшениці - Roche, J.; Didyk, N.P.; Ivanytska, B.O.; Zaimenko, N.V.; Chudovska, O.O. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2020)
The objective of this study was to assess the effects of the electromagnetic field of a Wi-Fi system and the experimental gadget M4 developed by SAS “IRDT” (France) on wheat seed germination, growth and photosynthetic activity of juvenile plants. Material and methods. The test-plants were grown under controlled conditions of light, temperature and humidity for eight days in a pot experiment modeling the following treatments: (1) without the electromagnetic field of Wi-Fi systems (control); (2) at a distance of 30 cm from the operating Wi-Fi router; (3) at a distance of 30 cm from operating Wi-Fi router and the experimental gadget M4. The test plant development and vitality were assessed using indices of seed germination, growth rates (shoot height, root length, number of lateral roots, shoot and root dry weights), photosynthetic pigment content in leaves, and the number of chloroplasts per a mesophyll cell in foliar tissues. Results. It was found that the electromagnetic field of the Wi-Fi router initially stimulated, but then suppressed the germination of seeds, reduced the growth of shoots and roots, the content of photosynthetic pigments and genesis of the chloroplasts in the mesophyll tissues in leaves of juvenile wheat plants. The root length was the most sensitive morphometric parameter to the electromagnetic field of the Wi-Fi router. The use of the gadget M4 completely compensated the negative impact of the Wi-Fi router on the seed germination, shoots growth, and partially compensated for the suppression of root growth, the genesis of the chloroplasts, chlorophyll a and b content in wheat leaves. Conclusion. The attenuation effect of gadget M4 against the damaging effect of electromagnetic fields of anthropogenic origin is promising, and further investigations are required to observe the effects in the long term, from sowing to maturity, including the next generation of seeds.